Synchronization of quaternion-valued BAM neural networks with time-varying delays: A matrix measure approach - Li, Lu; Tu, Zhengwen; Peng, Tao; Chen, Bing; Xiong, Jiang; Wang, Liangwei (Nonlinear Analysis: Modelling and Control, 2026)
This paper studies the global asymptotic synchronization (GAS) and global exponential synchronization (GES) problems of a class of quaternion-valued bidirectional associative memory neural networks (QVBAMNNs) with time-varying delays. Based on the matrix measure approach and Halanay inequality, sufficient conditions for GAS of unbounded time-varying delay system and GES of bounded time-varying delay system were established. Different from existing methods, this approach does not require the construction of Lyapunov functions and obtains the criteria for system synchronization expressed in terms of norms and measures. Finally, the validity of the proposed theoretical results and the feasibility of the control strategy are verified through numerical simulations.
Keywords: GAS; GES; QVBAMNNs; matrix measure approach; time-varying delays